Meningococcal septicaemia and dental complications: a literature review and two case reports - S. FAIBIS, R. WIDMER, S. SAPIR, B. PERETZ, & J. SHAPIRA (Paediatric Dentistry, 2005)
Neisseriae meningitidis is an anaerobic gram-negative cocci that is a frequent habitant of the human nasopharynx.